Surface treatment method of sintered aluminum foil

By using composite surfactant to treat the aluminum foil surface, the capacity reduction and leakage current problems caused by the agglomeration of aluminum powder and interlayer adhesion are solved, and higher capacity and lower leakage current are achieved, ensuring the flatness of the sintered foil and density.

CN119175370AActive Publication Date: 2024-12-24NANTONG HAIXING ELECTRONICS +2

Patent Information

Application Number
CN202411667903.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-24
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

During the preparation process, the capacity reduction and leakage current increase due to the prone to agglomeration of aluminum powder and interlayer adhesion.

Method used

Compound surfactants, including sodium dodecyl sulfate, isopropyl distearyloxy aluminate and 11-aminoundecyl trimethoxysilane, are uniformly mixed by high-speed disperser or high-speed ball mill to form The aluminum powder slurry is uniform and dried and sintered after coating the surface of the aluminum foil to reduce adhesion and shedding, forming a dense structure.

Benefits of technology

The capacity uniformity and thickness of the aluminum foil are improved, the leakage current is reduced, the flatness and density of the sintered foil are ensured, and the interlayer adhesion and leakage current are prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175370A_ABST
    Figure CN119175370A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolytic aluminum foil preparation, in particular to a surface treatment method for sintered aluminum foil. The surface treatment method of the sintered aluminum foil comprises the following steps of (1) aluminum foil surface treatment, (2) mixed slurry preparation, (3) slurry coated aluminum foil preparation, (4) rolling, (5) sintering and (6) formation. According to the surface treatment method of the sintered aluminum foil, uneven thickness and capacity of the aluminum foil caused by agglomeration of the aluminum powder are avoided, and the problems that in the rolling and sintering process of traditional aluminum foil, due to lamination of the aluminum foil, the aluminum foil and the aluminum foil are sintered together, interlayer adhesion is caused, the aluminum powder layer falls off, and the service life of the aluminum foil is prolonged are solved. And the capacity is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrolytic aluminum foil preparation, and in particular to a surface treatment method for sintered aluminum foil. Background Art

[0002] Aluminum electrolytic capacitors are widely used in industrial frequency conversion, inverters, 5G base stations, new energy charging piles and other fields, and are an important electronic device. Anode foil, as a key component, plays a decisive role in the quality control of aluminum electrolytic capacitors. At present, most domestic high-voltage anode foil manufacturing uses corrosion technology, which requires a sulfuric acid-hydrochloric acid system to chemically or electrochemically corrode the aluminum foil to generate a certain density of tunnel holes on the surface of the aluminum foil to increase its specific surface area. This method has been widely studied by many scholars, and its specific surface area increase is close to the theoretical limit. At the same time, a large amount of waste acid will be generated when using the sulfuric acid-hydrochloric acid system for production, which has great environmental pressure.

[0003] Aluminum powder sintered foil formed by sintering aluminum powder on both sides of aluminum foil has a higher specific surface area, and no waste acid or waste liquid is generated during its preparation, which becomes a new approach. Patent technical document CN116994882A discloses an anode foil and its preparation method and application. The preparation method described in the invention can form a uniformly dispersed aluminum paste, and the aluminum powder does not stratify or precipitate in the solvent, and the prepared anode foil has a higher electrostatic capacity; Patent technical document CN111463016A discloses a method for preparing a porous anode aluminum foil for electrolytic capacitors. The invention method also avoids the strong acid used in the traditional electrode liquid corrosion method, reducing environmental pollution.

[0004] However, during the preparation process, the micron aluminum powder is easy to agglomerate, and the uniformity of the aluminum powder slurry dispersion is difficult to ensure, which will lead to uneven thickness and capacity. In addition, during the winding and sintering process, due to the overlapping of aluminum foils, the aluminum foils will be sintered together, affecting the production yield. In addition, the aluminum powder layer falls off due to the adhesion between the layers, which also leads to a decrease in capacity. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a surface treatment method for sintered aluminum foil to solve the problem that the aluminum powder layer of the traditional sintered foil is easy to agglomerate and the interlayer adhesion causes the aluminum powder layer to fall off, resulting in reduced capacity and large leakage current.

[0006] Based on the above purpose, the present invention provides a surface treatment method for sintered aluminum foil, comprising the following steps: S1: Surface treatment of aluminum foil for standby use; S2: mixing aluminum powder, organic solvent, binder and composite surfactant, and uniformly mixing them by stirring with a high-speed disperser or by high-speed ball milling to obtain a mixed slurry; S3: uniformly coating the mixed slurry on the upper and lower surfaces of the aluminum foil substrate obtained in step S1, and then drying the mixed slurry to obtain a slurry-coated aluminum foil; S4: rolling the coated aluminum foil and then rolling it up to obtain a foil roll; S5: sintering the foil roll to obtain a sintered foil; S6: chemically forming the sintered foil to obtain a chemically formed foil; The composite surfactant is prepared by mixing sodium dodecyl sulfate, isopropyl distearoyloxyaluminate and 11-aminoundecyltrimethoxysilane in a weight ratio of 9-10:0.8-0.9:0.1-0.2 and stirring them uniformly.

[0007] Preferably, the surface treatment in step S1 is one of mechanical polishing, plasma gas treatment, and acid-base immersion.

[0008] Preferably, when the surface treatment is plasma gas treatment, the plasma gas is O 2 , H 2 O, O 3 , H 2 O 2 , one or more in the air.

[0009] Preferably, when the surface treatment is acid-base immersion, the liquid used for immersion is water, NaOH, H 2 O 2 , ammonia, H 2 SO 4 One or more of the .

[0010] Preferably, when the surface treatment is acid-base immersion, the liquid temperature is 60-120° C. and the immersion time is 5-20 min.

[0011] Preferably, the weight ratio of the aluminum powder to the adhesive in step S2 is 10-100:1.

[0012] Preferably, in step S2, the weight ratio of aluminum powder to complex surfactant is 20-500:1.

[0013] Preferably, the organic solvent in step S2 is one of ethanol, ethylene glycol, acetone, N-methylpyrrolidone, and N,N-dimethylformamide.

[0014] Preferably, the adhesive in step S2 is one of epoxy resin, polyvinyl alcohol, polycarbosilane, polyacrylamide, phenolic resin, cyanoacrylate, polyurethane, polyvinylidene fluoride, and acrylic resin.

[0015] Preferably, the drying process in step S3 is a temperature-controlled drying process, specifically, in a vacuum environment, the temperature is raised to 60-120° C. at 2-3° C. / min, and the drying time is 4-5 h.

[0016] Preferably, the coating thickness of the mixed slurry in step S3 is 10-100 μm.

[0017] Preferably, the specific operation of sintering in step S5 is to heat to 300-450° C. within 1.5-2 hours under nitrogen atmosphere, keep warm for 1.5-2 hours, and then heat to 550-640° C. within 1.5-2 hours under argon atmosphere, keep warm for 1.5-2 hours.

[0018] Preferably, the temperature is raised to 300-450° C. within 1.5-2 h, and the process can also be carried out under air, argon or vacuum conditions.

[0019] Preferably, the temperature is raised to 550-640° C. within 1.5-2 h, and the process can also be carried out under nitrogen or vacuum conditions.

[0020] Preferably, the formation voltage in step S5 is 520V.

[0021] Beneficial effects of the present invention: When the composite surfactant of the present invention contains isopropyl distearoyloxyaluminate, the aluminum powders are more tightly bound together, thereby reducing the possibility of aluminum powders between layers sticking to each other when the whole roll is sintered, reducing the shedding of the aluminum powder layer caused by the sticking, so that its capacity is guaranteed. At the same time, due to the close connection between the aluminum powders, a denser structure can be formed during the sintering process, which can ensure that the layers of the foil roll will not stick to each other when it is peeled off.

[0022] When the composite surfactant of the present invention contains 11-aminoundecyltrimethoxysilane, the aluminum powder has better dispersibility and is not easy to agglomerate, and the surface of the sintered foil obtained after sintering is smoother and the thickness is more uniform.

[0023] When the composite surfactant of the present invention contains 11-aminoundecyltrimethoxysilane and isopropyl distearoyloxyaluminate, hydrophilic long chains and hydrophobic long chains can be attached to the surface of aluminum powder. The hydrophilic and hydrophobic surfaces and the mutual entanglement between the long chains can improve the capacity of the aluminum foil, and the smooth and dense oxide film can also prevent the increase of leakage current. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description. Figure 1 This is a scanning electron microscope image of the sample obtained in Example 2 of the present invention; Figure 2 This is a scanning electron microscope image of the sample obtained in Comparative Example 4 of the present invention; Figure 3 This is a direct photograph of the sample obtained in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0026] Embodiment 1: A surface treatment method for sintered aluminum foil, the specific steps are as follows: (1) Soak the aluminum foil in a 10% ammonia solution at 60°C for 5 minutes, wash it with pure water, and dry it for later use; (2) 9 g of sodium dodecyl sulfate, 0.8 g of isopropyl distearoyloxyaluminate and 0.1 g of 11-aminoundecyltrimethoxysilane were mixed and stirred to obtain a composite surfactant; (3) 100 g aluminum powder, 200 ml NMP solvent, 1 g polyacrylamide and 0.5 g composite surfactant were mixed, stirred evenly, and then ground under a high-speed ball mill for 1 h to obtain a mixed slurry; (4) The mixed slurry is evenly coated on the upper and lower surfaces of the aluminum foil substrate in step (1). After coating, the temperature is raised to 60°C at a rate of 2°C / min in a vacuum environment and dried for 4 hours to obtain a coated aluminum foil with a coating thickness of 60 μm; (5) rolling the coated aluminum foil and then rolling it up to obtain a foil roll; (6) In a nitrogen atmosphere, the foil roll was heated to 300°C within 1.5 hours and kept at this temperature for 1.5 hours. Then, in an argon atmosphere, the foil roll was heated to 550°C within 1.5 hours and kept at this temperature for 1.5 hours to obtain a sintered foil. (7) The sintered foil is washed with pure water and then chemically processed using a conventional chemical process at a voltage of 520 Vf to obtain a chemically processed foil.

[0027] Embodiment 2: A surface treatment method for sintered aluminum foil, the specific steps are as follows: (1) Soak the aluminum foil in a 10% ammonia solution at 90°C for 15 minutes, take it out and wash it with pure water, dry it and set it aside for use; (2) 9.5 g of sodium dodecyl sulfate, 0.85 g of isopropyl distearoyloxyaluminate and 0.15 g of 11-aminoundecyltrimethoxysilane were mixed and stirred to obtain a composite surfactant; (3) 100 g aluminum powder, 200 ml NMP solvent, 5 g polyacrylamide and 3 g composite surfactant were mixed, stirred evenly, and then ground under a high-speed ball mill for 1 h to obtain a mixed slurry; (4) The mixed slurry is evenly coated on the upper and lower surfaces of the aluminum foil substrate in step (1). After coating, the temperature is raised to 90°C at a rate of 2.5°C / min in a vacuum environment and dried for 5 hours to obtain a coated aluminum foil with a coating thickness of 60 μm. (5) rolling the coated aluminum foil and then rolling it up to obtain a foil roll; (6) In a nitrogen atmosphere, the foil roll was heated to 400°C within 2 hours and kept at this temperature for 2 hours, and then in an argon atmosphere, the foil roll was heated to 600°C within 2 hours and kept at this temperature for 2 hours to obtain a sintered foil; (7) The sintered foil is washed with pure water and then chemically processed using a conventional chemical process at a voltage of 520 Vf to obtain a chemically processed foil.

[0028] Embodiment 3: A surface treatment method for sintered aluminum foil, the specific steps are as follows: (1) Soak the aluminum foil in a 10% ammonia solution at 120°C for 20 minutes, take it out and wash it with pure water, dry it and set it aside for use; (2) 10 g of sodium dodecyl sulfate, 0.9 g of isopropyl distearoyloxyaluminate and 0.2 g of 11-aminoundecyltrimethoxysilane were mixed and stirred to obtain a composite surfactant; (3) 100 g aluminum powder, 200 ml NMP solvent, 10 g polyacrylamide and 5 g composite surfactant were mixed, stirred evenly, and then ground under a high-speed ball mill for 1 h to obtain a mixed slurry; (4) The mixed slurry is evenly coated on the upper and lower surfaces of the aluminum foil substrate in step (1). After coating, the temperature is raised to 120° C. at a rate of 3° C. / min in a vacuum environment and dried for 5 h to obtain a coated aluminum foil with a coating thickness of 60 μm. (5) rolling the coated aluminum foil and then rolling it up to obtain a foil roll; (6) In a nitrogen atmosphere, the foil roll was heated to 450°C within 2 hours and kept at this temperature for 2 hours, and then in an argon atmosphere, the temperature was raised to 640°C within 2 hours and kept at this temperature for 2 hours to obtain a sintered foil; (7) The sintered foil is washed with pure water and then chemically processed using a conventional chemical process at a voltage of 520 Vf to obtain a chemically processed foil.

[0029] Comparative Example 1: A surface treatment method for sintered aluminum foil, the specific steps are as follows: The difference from Example 2 is that the composition of the composite surfactant is 9.5g sodium dodecyl sulfate, 0.85g aluminum triacetylacetonate and 0.15g 11-aminoundecyltrimethoxysilane, and the specific steps are as follows: (1) Soak the aluminum foil in a 10% ammonia solution at 90°C for 15 minutes, take it out and wash it with pure water, dry it and set it aside for use; (2) 9.5 g of sodium dodecyl sulfate, 0.85 g of aluminum triacetylacetonate and 0.15 g of 11-aminoundecyltrimethoxysilane were mixed and stirred to obtain a composite surfactant; (3) 100 g aluminum powder, 200 ml NMP solvent, 5 g polyacrylamide and 3 g composite surfactant were mixed, stirred evenly, and then ground under a high-speed ball mill for 1 h to obtain a mixed slurry; (4) The mixed slurry is evenly coated on the upper and lower surfaces of the aluminum foil substrate in step (1). After coating, the temperature is raised to 90°C at a rate of 2.5°C / min in a vacuum environment and dried for 5 hours to obtain a coated aluminum foil with a coating thickness of 60 μm. (5) rolling the coated aluminum foil and then rolling it up to obtain a foil roll; (6) In a nitrogen atmosphere, the foil roll was heated to 400°C within 2 hours and kept at this temperature for 2 hours, and then in an argon atmosphere, the foil roll was heated to 600°C within 2 hours and kept at this temperature for 2 hours to obtain a sintered foil; (7) The sintered foil is washed with pure water and then chemically processed using a conventional chemical process at a voltage of 520 Vf to obtain a chemically processed foil.

[0030] Comparative Example 2: A surface treatment method for sintered aluminum foil, the specific steps are as follows: The difference from Example 2 is that the composition of the composite surfactant is 9.5g of sodium dodecyl sulfate, 0.85g of isopropyl distearoyloxyaluminate and 0.15g of dodecyltrimethoxysilane, and the specific steps are as follows: (1) Soak the aluminum foil in a 10% ammonia solution at 90°C for 15 minutes, take it out and wash it with pure water, dry it and set it aside for use; (2) 9.5 g of sodium dodecyl sulfate, 0.85 g of isopropyl distearoyloxyaluminate and 0.15 g of dodecyl trimethoxysilane were mixed and stirred to obtain a composite surfactant; (3) 100 g aluminum powder, 200 ml NMP solvent, 5 g polyacrylamide and 3 g composite surfactant were mixed, stirred evenly, and then ground under a high-speed ball mill for 1 h to obtain a mixed slurry; (4) The mixed slurry is evenly coated on the upper and lower surfaces of the aluminum foil substrate in step (1). After coating, the temperature is raised to 90°C at a rate of 2.5°C / min in a vacuum environment and dried for 5 hours to obtain a coated aluminum foil with a coating thickness of 60 μm. (5) rolling the coated aluminum foil and then rolling it up to obtain a foil roll; (6) In a nitrogen atmosphere, the foil roll was heated to 400°C within 2 hours and kept at this temperature for 2 hours, and then in an argon atmosphere, the foil roll was heated to 600°C within 2 hours and kept at this temperature for 2 hours to obtain a sintered foil; (7) The sintered foil is washed with pure water and then chemically processed using a conventional chemical process at a voltage of 520 Vf to obtain a chemically processed foil.

[0031] Comparative Example 3: A surface treatment method for sintered aluminum foil, the specific steps are as follows: The difference from Example 2 is that the composition of the composite surfactant is 9.5g sodium dodecyl sulfate, 0.85g isopropyl distearoyloxyaluminate and 0.15g methyltrimethoxysilane, and the specific steps are as follows: (1) Soak the aluminum foil in a 10% ammonia solution at 90°C for 15 minutes, take it out and wash it with pure water, dry it and set it aside for use; (2) 9.5 g of sodium dodecyl sulfate, 0.85 g of isopropyl distearoyloxyaluminate and 0.15 g of methyl trimethoxybenzene were mixed and stirred to obtain a composite surfactant; (3) 100 g aluminum powder, 200 ml NMP solvent, 5 g polyacrylamide and 3 g composite surfactant were mixed, stirred evenly, and then ground under a high-speed ball mill for 1 h to obtain a mixed slurry; (4) The mixed slurry is evenly coated on the upper and lower surfaces of the aluminum foil substrate in step (1). After coating, the temperature is raised to 90°C at a rate of 2.5°C / min in a vacuum environment and dried for 5 hours to obtain a coated aluminum foil with a coating thickness of 60 μm. (5) rolling the coated aluminum foil and then rolling it up to obtain a foil roll; (6) In a nitrogen atmosphere, the foil roll was heated to 400°C within 2 hours and kept at this temperature for 2 hours, and then in an argon atmosphere, the foil roll was heated to 600°C within 2 hours and kept at this temperature for 2 hours to obtain a sintered foil; (7) The sintered foil is washed with pure water and then chemically processed using a conventional chemical process at a voltage of 520 Vf to obtain a chemically processed foil.

[0032] Comparative Example 4: A surface treatment method for sintered aluminum foil, the specific steps are as follows: The difference from Example 2 is that the composite surfactant is composed of 9.5 g sodium dodecyl sulfate, 0.85 g aluminum triacetylacetonate and 0.15 g methyltrimethoxysilane, and the specific preparation steps are as follows: (1) Soak the aluminum foil in a 10% ammonia solution at 90°C for 15 minutes, take it out and wash it with pure water, dry it and set it aside for use; (2) 9.5 g of sodium dodecyl sulfate, 0.85 g of aluminum triacetylacetonate and 0.15 g of methyl trimethoxybenzene were mixed and stirred to obtain a composite surfactant; (3) 100 g aluminum powder, 200 ml NMP solvent, 5 g polyacrylamide and 3 g composite surfactant were mixed, stirred evenly, and then ground under a high-speed ball mill for 1 h to obtain a mixed slurry; (4) The mixed slurry is evenly coated on the upper and lower surfaces of the aluminum foil substrate in step (1). After coating, the temperature is raised to 90°C at a rate of 2.5°C / min in a vacuum environment and dried for 5 hours to obtain a coated aluminum foil with a coating thickness of 60 μm. (5) rolling the coated aluminum foil and then rolling it up to obtain a foil roll; (6) In a nitrogen atmosphere, the foil roll was heated to 400°C within 2 hours and kept at this temperature for 2 hours, and then in an argon atmosphere, the foil roll was heated to 600°C within 2 hours and kept at this temperature for 2 hours to obtain a sintered foil; (7) The sintered foil is washed with pure water and then chemically processed using a conventional chemical process at a voltage of 520 Vf to obtain a chemically processed foil.

[0033] Performance Testing Specific volume: According to the EIAJ RC-2364A standard method, the specific volume tester is used for measurement. The test results are shown in Table 1; Leakage current: Use TH1500-3 aluminum foil characteristic intelligent test system to test the current value 180s after the aluminum foil withstand voltage reaches 90%, which is its leakage current.

[0034] Table 1 Performance test results

[0035] Data analysis: It can be seen from Examples 1-3 in Table 1 that the surface treatment method of the sintered aluminum foil of the present invention, under a withstand voltage of 520V, the obtained aluminum foil has excellent capacity and low leakage current regardless of the outer ring or the inner ring, which solves the problem of traditional sintered aluminum foil due to easy agglomeration of aluminum powder and sintering of aluminum foil together due to the stacking of aluminum foils, as well as the shedding of aluminum powder layer caused by interlayer adhesion, which in turn leads to increased capacity and leakage current of the aluminum foil.

[0036] It can be seen from Example 2 and Comparative Example 1 in Table 1 that when aluminum triacetylacetonate is used instead of isopropyl distearoyloxyaluminate, its specific volume is slightly reduced. This may be because when isopropyl distearoyloxyaluminate is connected to the surface of aluminum powder through a chemical reaction, its long chain can be entangled with the long chain of 11-aminoundecyltrimethoxysilane attached to the surface, so that the aluminum powder is more tightly bonded, thereby reducing the possibility of aluminum powder adhesion between layers when the whole roll is sintered, and reducing the shedding of aluminum powder layers caused by adhesion, so that its capacity is guaranteed. At the same time, due to the close connection between aluminum powders, a denser structure can be formed during the sintering process, which ensures that the sintered foil has a lower leakage current and can also ensure that the foil roll will not cause mutual adhesion between layers when peeling.

[0037] It can be seen from Example 2 and Comparative Example 1 in Table 1 that when dodecyltrimethoxysilane is used instead of 11-aminoundecyltrimethoxysilane, its specific capacity and leakage current both deteriorate to a certain extent. This may be because when the coupling agent is attached to the surface of the aluminum powder, the aluminum powder with hydrophilic groups on the surface and the aluminum powder with hydrophobic groups on the surface have better dispersibility than the aluminum powder with hydrophobic groups on the surface, and are not easy to agglomerate. As a result, the surface of the sintered foil obtained after sintering is smoother and the thickness is more uniform, so that its capacity is larger; and the flat and dense oxide film on the surface can also prevent the increase of leakage current.

[0038] It can be seen from Example 2 and Comparative Examples 3 and 4 in Table 1 that when isopropyl distearoyloxyaluminate and 11-aminoundecyltrimethoxysilane are used, hydrophilic long chains and hydrophobic long chains are attached to the surface of the aluminum powder. The hydrophilic and hydrophobic surfaces and the mutual entanglement between the long chains can improve the capacity of the aluminum foil, and the smooth and dense oxide film can also prevent the increase of leakage current.

[0039] pass Figure 1 and 2 It can also be seen from the scanning electron microscope that the aluminum powder on the surface of the aluminum foil obtained in Example 2 of the present invention is dispersed more evenly.

[0040] pass Figure 3 It can be seen that the sample obtained in Comparative Example 4 exhibits severe adhesion between the aluminum foil layers during winding and sintering.

[0041] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A surface treatment method for sintered aluminum foil, characterized in that: The following steps are involved: S1: Surface treatment of aluminum foil for standby use; S2: mixing aluminum powder, organic solvent, adhesive and composite surfactant, and mixing them evenly to obtain a mixed slurry; S3: uniformly coating the mixed slurry on the upper and lower surfaces of the aluminum foil substrate obtained in step S1, and drying to obtain a slurry-coated aluminum foil; S4: rolling the slurry-coated aluminum foil and then rolling it up to obtain a foil roll; S5: sintering the foil roll to obtain a sintered foil; S6: chemically forming the sintered foil to obtain a chemically formed foil; The composite surfactant is prepared by mixing sodium dodecyl sulfate, isopropyl distearoyloxyaluminate and 11-aminoundecyltrimethoxysilane in a weight ratio of 9-10:0.8-0.9:0.1-0.2 and stirring them uniformly.

2. The surface treatment method of sintered aluminum foil according to claim 1, characterized in that: The surface treatment in step S1 is one of mechanical polishing, plasma gas treatment and acid-base immersion.

3. The surface treatment method of sintered aluminum foil according to claim 1, characterized in that: In step S2, the weight ratio of the aluminum powder to the adhesive is 10-100:1; the weight ratio of the aluminum powder to the composite surfactant is 20-500:

1.

4. The surface treatment method of sintered aluminum foil according to claim 1, characterized in that: The organic solvent in step S2 is one of ethanol, ethylene glycol, acetone, N-methylpyrrolidone, and N,N-dimethylformamide.

5. The surface treatment method of sintered aluminum foil according to claim 1, characterized in that: The adhesive in step S2 is one of epoxy resin, polyvinyl alcohol, polycarbosilane, polyacrylamide, phenolic resin, cyanoacrylate, polyurethane, polyvinylidene fluoride, and acrylic resin.

6. The surface treatment method of sintered aluminum foil according to claim 1, characterized in that: The drying in step S3 is temperature-controlled drying, specifically, in a vacuum environment, the temperature is raised to 60-120° C. at 2-3° C. / min, and the drying time is 4-5 h.

7. The surface treatment method of sintered aluminum foil according to claim 1, characterized in that: The specific operation of sintering in step S5 is to heat up to 300-450° C. within 1.5-2 hours, keep warm for 1.5-2 hours, and then heat up to 550-640° C. within 1.5-2 hours under argon atmosphere, and keep warm for 1.5-2 hours.

Citation Information

Patent Citations

  • Preparation method of porous anode aluminum foil for electrolytic capacitor

    CN111463016A

  • Anode foil and preparation method and application thereof

    CN116994882A

  • Surface treated copper foil, surface treated copper foil with very thin primer resin layer, method for manufacturing the surface treated copper foil, and method for manufacturing the surface treated c

    CN101528981A

  • Metallic foil with adhesion promoting layer

    CN1106977A

  • Preparation method of wear-resistant alloy coating for scraper of drum filter

    CN114774915A

Cited By

  • Preparation method of powder sintered foil

    CN119368744A

  • A method for preparing powder sintered foil

    CN119368744B